The effect of Perilla frutescens leaf on 1, 2-dimethylhydrazine-induced initiation of colon carcinogenesis in rats - Chakkrit Khanaree (2018)
© 2018 Wiley Periodicals, Inc. In this study, the chemopreventive properties of Perilla frutescens leaf extract (PLE) on rat colon carcinogenesis were investigated during initiation and postinitiation stages. Rats were fed orally by 50 and 500 mg/kg bw of PLE continuously from 1 week before subcutaneously injection of 1,2-dimethylhydrazine (DMH) until the end of experiment. PLE administration reduced the aberrant crypt foci (ACF) number in DMH-treated rats through the inhibition of hepatic cytochrome P4502E1 (CYP2E1) and bacterial β-glucuronidase activity in the colonic lumen. These events led to the reduction of DNA methylation in colonic epithelial cells. For the postinitiation model, rats were injected (s.c.) with DMH, followed by PLE administration until the end of experiment. PLE administration also reduced the ACF number in DMH-induced rats, resulting from apoptosis induction and reduction of proliferation in colon crypt cells. These studies demonstrated that perilla leaf could inhibit ACF formation and progression in DMH-initiated colon carcinogenesis in rats. Practical applications: This study revealed the inhibitory effect of PLE on chemical-induced colon carcinogenesis in rats. Altogether, our data supported that PLE acts as a chemopreventive agent for colon cancer. Thus, PLE might be developed as food supplement or functional tea for colon cancer prevention.